2013
DOI: 10.5120/14567-2688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MAC Layer on AODV and LAR Routing Protocols in MANETs

Abstract: A Mobile Ad hoc Network is a type of ad hoc network. It can change its location configuration dynamically. It is an infrastructure-less network. Due to the complex nature of MANETS, their development processes face several challenges. One of such key challenge is routing. Several routing protocols have already been proposed for MANETs. This paper examines the impact of MAC protocols 802.11 and CSMA on the two on demand routing protocols AODV and LAR in MANETs with varying Node density in the network. Number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Srivastava et al [9] presented some open challenges and new opportunities for cross-layer design. Venkataramana et al [3] presented the impact of MAC layer protocol on the performance routing protocols in Manets and the simulation experiments found that both 802. 11 and CSMA is suitable for AODV where as only 802.…”
Section: Literature Surveymentioning
confidence: 97%
See 1 more Smart Citation
“…Srivastava et al [9] presented some open challenges and new opportunities for cross-layer design. Venkataramana et al [3] presented the impact of MAC layer protocol on the performance routing protocols in Manets and the simulation experiments found that both 802. 11 and CSMA is suitable for AODV where as only 802.…”
Section: Literature Surveymentioning
confidence: 97%
“…Pro-active routing is also called Table driven routing where as re-active routing is called On-demand and dynamic routing. Reactive routing protocols are popular in MANETs because they are more scalable and less overhead on the network [2][3][4]. AODV, DSR and DYMO are popular reactive routing protocols.…”
Section: Introductionmentioning
confidence: 99%
“…There are a plethora of MAC protocols proposed in the literature. Prior studies have investigated previous MAC layers 4 impact on some routing protocols, such as 802.11 and CSMA on AODV and LAR, but not TSCH. Therefore, in this paper, we investigate the use of TSCH with AODV and compared it with traditional CSMA.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that routing protocols shows better performance in Random way point mobility model [1]. Muhammad Ibrahim et al [2] presented certain QoS models that provide architecture for providing QoS to the mobile nodes in the MANETs. Hanzo, L. and Tafazolli et al [3] presented problems that may occur in providing QoS to Mobile nodes in Mobile Ad-hoc networks and solution for managing those problems, like dynamic topologies, that change continuously and unpredictable at any time.…”
Section: Related Workmentioning
confidence: 99%
“…Routing protocols for ad-hoc network can be categorized in to three categories. The three classifications of routing algorithms are Reactive, Proactive and Hybrid routing protocols [2]. This paper evaluates the performance of routing protocols under propagation models using NS-2.…”
Section: Introductionmentioning
confidence: 99%